Diffusion‐weighted imaging and diagnosis of transient ischemic attack. Issue 1 (2nd January 2014) - Brazzelli, Miriam; Chappell, Francesca M.; Miranda, Hector; Shuler, Kirsten; Dennis, Martin; Sandercock, Peter A. G.; Muir, Keith; Wardlaw, Joanna M.
<x xml:space="preserve">Abstract</x> Objective Magnetic resonance (MR) diffusion‐weighted imaging (DWI) is sensitive to small acute ischemic lesions and might help diagnose transient ischemic attack (TIA). Reclassification of patients with TIA and a DWI lesion as "stroke" is under consideration. We assessed DWI positivity in TIA and implications for reclassification as stroke. Methods We searched multiple sources, without language restriction, from January 1995 to July 2012. We used PRISMA guidelines, and included studies that provided data on patients presenting with suspected TIA who underwent MR DWI and reported the proportion with an acute DWI lesion. We performed univariate random effects meta‐analysis to determine DWI positive rates and influencing factors. Results We included 47 papers and 9, 078 patients (range = 18–1, 693). Diagnosis was by a stroke specialist in 26 of 47 studies (55%); all studies excluded TIA mimics. The pooled proportion of TIA patients with an acute DWI lesion was 34.3% (95% confidence interval [CI] = 30.5–38.4, range = 9–67%; I2 = 89.3%). Larger studies (n > 200) had lower DWI‐positive rates (29%; 95% CI = 23.2–34.6) than smaller (n < 50) studies (40.1%; 95% CI = 33.5–46.6%; p = 0.035), but no other testable factors, including clinician speciality and time to scanning, reduced or explained the 7‐fold DWI‐positive variation. Interpretation The commonest DWI finding in patients with definite TIA is a negative scan. Available data do not explain why ⅔ of patients with definite specialist‐confirmed TIA have negative DWI findings. Until these factors are better understood, reclassifying DWI‐positive TIAs as strokes is likely to increase variance in estimates of global stroke and TIA burden of disease. ANN NEUROL 2014;75:67–76